SIMULATION OF IONOSPHERIC HEATING BASED ON SAMI2 MODEL. Issue 4 (July 2016) - Xing, MENG; Han‐Xian, FANG; Li‐Bin, WENG; Si‐Cheng, WANG
Abstract: With artificial heating term ( Q hf ) added in the electron energy equation of SAMI2 model, the disturbance amplitude of electron temperature and density along field line is simulated. The effects of disturbances under different heating conditions are also compared. The results show that the terrestrial ionospheric plasma can be heated by powerful high‐frequency radio waves, which can result in the rising of the temperature of electron in the whole field line, especially at the heated spot where electron temperature enhances more than 3 times; the pressure balance is broken as the increase in the electron temperature, which leads to plasma diffusion and then perturbation of electron density occurred; electron density gradient perpendicular to magnetic field line changes in accordance with the perturbation of electron density; the perturbation amplitude of electron temperature and density decreases during the heating time, which gradually becomes saturated. Electron temperature and density have a nonlinear relationship with the intensity of heating source.